MENGGALI ASPEK PSIKOLINGUISTIK DALAM PEMBELAJARAN BAHASA ASING BAGI PENYANDANG TUNARUNGU: TANTANGAN SOLUSI - Bastian Sirait, Dicky; Najwa Aldisa, Olivia; Abdullah Harras, Kholid (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This research aims to describe the understanding and obstacles faced by hearing-impaired individuals in foreign language learning, particularly English, within the field of psycholinguistics. The subject of this research is a hearing-impaired student named Nazwa Aprilia at the Universitas Pendidikan Indonesia. The method used in the research is descriptive qualitative with techniques such as interviews, documentation, and observation. The results of this study show the problems faced by hearing-impaired individuals in learning foreign languages from several perspectives, namely 1) objectives; 2) learners; 3) teachers; and 4) environmental factors. The environmental factor is the most influential indicator in foreign language learning for hearing-impaired individuals. In line with that, the researchers recommend practical solutions to minimize the difficulties.